SME development in Malaysia: challenges of SMES manufacturing sector to go abroad / Mohamad Shafik Ismail - Ismail, Mohamad Shafik (Faculty of Business and Management, 2011)
The paper presented the challenges and barriers of Small Medium Enterprises (SMEs) which involve in manufacturing to expand their business abroad. The purpose of the study is to gain understanding towards the challenges that must be faced by manufacturing SMEs thus, order to help them develop strategies in global market. It will also help financial institutions, trade agencies and trade associations to run their activities efficiently. Hence, these agencies can provide sufficient services to help the local SMEs to go abroad. In order to create understanding, this study use secondary data in order to collect reliable data. The previous studies were reviewed and put in literature review section. Interviews were conducted with related institutions which have relation with Malaysia manufacturing SMEs. The information obtained from both primary and secondary sources have been analyzed to identify the factors that give challenge for Malaysia manufacturing SMEs abroad. At the end of this study, it was found that there are several challenges of SMEs to go abroad. The most frequent discussion is inter-firm relationship. The other challenges are host government policy, financial disability and competition among industry players. The important of knowledge and technological constrain also can give impact to the SMEs abroad. This study also recommend SMEs to seek for linkages abroad and the role of development banks should be intensified for SMEs to enhance. This study also recommends the government to take further action to help the SMEs in the other market. The SMEs also can use branding strategies and increase their knowledge in order to success in future either locally or globally.